2018
DOI: 10.7554/elife.32948
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNA-nucleated heterochromatin spreading is intrinsically labile and requires accessory elements for epigenetic stability

Abstract: The heterochromatin spreading reaction is a central contributor to the formation of gene-repressive structures, which are re-established with high positional precision, or fidelity, following replication. How the spreading reaction contributes to this fidelity is not clear. To resolve the origins of stable inheritance of repression, we probed the intrinsic character of spreading events in fission yeast using a system that quantitatively describes the spreading reaction in live single cells. We show that spread… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
159
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(174 citation statements)
references
References 79 publications
9
159
0
Order By: Relevance
“…We hypothesized that for gene barrier activity to be ineffective in the 3′ orientation, heterochromatin must be able to at least partially invade the gene from the 3′ end, which is depleted for H3K4me3 [32]. This would be consistent with our previous results that showed that a 3′ oriented reporter can experience intermediate repression, which correlated with intermediate levels of RNA, H3K4me3, and H3K9me2 [33]. Partial invasion may then lead to transcriptional silencing, which would inherently down-regulate H3K4me.…”
Section: Invasion Into the Gene 3′ Is Sufficient For Silencing And Resupporting
confidence: 82%
See 4 more Smart Citations
“…We hypothesized that for gene barrier activity to be ineffective in the 3′ orientation, heterochromatin must be able to at least partially invade the gene from the 3′ end, which is depleted for H3K4me3 [32]. This would be consistent with our previous results that showed that a 3′ oriented reporter can experience intermediate repression, which correlated with intermediate levels of RNA, H3K4me3, and H3K9me2 [33]. Partial invasion may then lead to transcriptional silencing, which would inherently down-regulate H3K4me.…”
Section: Invasion Into the Gene 3′ Is Sufficient For Silencing And Resupporting
confidence: 82%
“…To investigate ectopic invasion of heterochromatin, we employed our previously described heterochromatin spreading sensor (HSS) [33,34] in the euchromatic region proximal to the MAT Inverted Repeat Right (IR-R) boundary [35]. This HSS system contains two central components: (1) the spreading sensor, a monomeric Kusabira-Orange 2 fluorescent protein driven by the validated ade6 promoter, hereafter referred to as "orange", integrated 0.7kb outside IR-R, and (2) the control, a E2Crimson fluorescent protein driven by the same promoter, hereafter referred to as "red", integrated at a constitutive euchromatic locus [33] (Figure 1A). We use flow cytometry to capture information from tens of thousands of single cells.…”
Section: Genes Can Function As a Barrier To Heterochromatin Spreadingmentioning
confidence: 99%
See 3 more Smart Citations